Design and Analysis of a Hybrid Excited Linear Machine with Characteristic of Air Gap Balanced - Guo, Rong; Guo, Baocheng; Zhang, Fengyu; Shen, Yuxin (Institute of Electrical and Electronics Engineers, 2024)
The existing guiding technology of ropeless lifting system has the problem of difficult to ensure the air gap uniform during dynamic operation, which causes the vibration and noise between wheel and rail. To address this issue, a novel hybrid excited flux-reversal linear machine with characteristic of air gap balanced (HEFRLM-AGB) is proposed in this paper. Due to the space confliction between armature and field windings in conventional hybrid-excited machine, the partitioned primary structure with permanent magnet inset is employed to reduced flux leakage and enhance the power density, meanwhile, the two field windings are applied to flexible modulate the air gap magnetic field. Firstly, the topology, operation principle and flux regulation mechanism are introduced. Then, considering the complex magnetic path, the improved Taguchi multi-objective optimization method is used to obtain the optimal deterministic values. Finally, the machine design and optimization method are evaluated and verified by both finite element analysis and prototype experiments.